2020
DOI: 10.1021/acs.iecr.0c00546
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Emissive Coating Films Prepared from Water-Borne Latexes of Acrylate–Vinylidene Chloride Copolymers: Their Room-Temperature Phosphorescence Properties and Sensing Abilities toward Solvents

Abstract: Materials with a room-temperature phosphorescence (RTP) property have wide application fields. For practical applications, it is highly desirable that only a small amount of RTP phosphors was attached to the widely used hydrophobic polymers, especially the coating polymers, to avoid impairing the physical properties of polymers while reserving RTP function. In this work, aqueous latexes of copolymers of acrylate and vinylidene chloride (VDC) were prepared through the green emulsion polymerization in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Liu and Chen et al also reported polymer lms to detect organic solvents, employing the acrylate-vinylidene chloride copolymers (acrylate-VDC) as the polymer matrix and N-hydroxyethyl 4bromo-1,8-naphthalimide (85) as the OPL phosphor. 111 As shown in Fig. 12b, the hydrophobic polymer matrix is immiscible with polar protic solvents, and the lm keeps the OPL emission in contact with alcohol.…”
Section: Organic Solvent Sensingmentioning
confidence: 98%
“…Liu and Chen et al also reported polymer lms to detect organic solvents, employing the acrylate-vinylidene chloride copolymers (acrylate-VDC) as the polymer matrix and N-hydroxyethyl 4bromo-1,8-naphthalimide (85) as the OPL phosphor. 111 As shown in Fig. 12b, the hydrophobic polymer matrix is immiscible with polar protic solvents, and the lm keeps the OPL emission in contact with alcohol.…”
Section: Organic Solvent Sensingmentioning
confidence: 98%